Research of Alternative Energy Sources for Railway Vehicles - Sadílek, Ondřej; Lelek, Tomáš; Sýkora, Petr; Doleček, Radovan (IEEE (Institute of Electrical and Electronics Engineers), 2016)
This paper describes research activities that have Department of Electrical and Electronic Engineering and Signaling in Transport done in area of control, accumulators and photovoltaic feeding of railway vehicles - the biggest part is focused on experimental research done on narrow-track experimental railway vehicle owned by the department. The paper deals with the description of the experimental vehicle which means the concrete topology of electric drive and the structure of sourcing system (Li-ion LiFePO4 battery and photovoltaic cells). In the article are published the existing results and defined next needed tests.
Výzkum alternativních zdrojů pro kolejová vozidla
Keywords: railway vehicle; accumulator; charging; photovoltaic panel; drážní vozidlo; akumulátor; nabíjení; fotovoltaický panel